Digital media literacy, school and contemporary parenting - Ciboci, Lana (Array, 2019)
Today’s societies live in a world where the media construct reality, which also affects each individual media user. Children and their parents spend most of their time with digital media and contents. Therefore, researchers emphasize the importance of digital literacy of media users. They analyse new phenomena, challenges and risks associated with the anthropological, cognitive and social development of children and young people. An important role in media and digital education is played not only by teachers and schools, but also by parents and family. The aim of this paper is to present and analyse the theoretical approaches to digital media literacy, so-called digital parenting, and to interpret the results of the latest research in Croatia devoted to the digital habits of parents, their attitudes towards parental mediation strategies as well as to their satisfaction with the programmes of media literacy in the education system.